2023
DOI: 10.1038/s41598-023-34972-5
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping floral traits and essential oil profiling revealed considerable variations in clonal selections of damask rose (Rosa damascena Mill.)

Abstract: Damask rose (Rosa damascena Mill.) is a high-value aromatic plant species belonging to the family Rosaceae. It is being cultivated throughout the world for rose essential oil production. Besides its higher demand in the aromatic and cosmetic industry, the essential oil obtained has many pharmacological and cytotoxic activities. The primary concern of growers with the available varieties of damask rose is short flowering duration, low essential oil content and unstable yield. Thus, there is a requirement for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…At flowering, seven metabolites were found to be accumulated, including α-tocopherol, γ-tocopherol, methyl hendecanoic acid, ursolic acid, oleate, 1-docosene, and 9-eicosene (Figure 1C). Volatiles such as 1-docosene and 9-eicosene have been found in the essential oils of Tamarix dioica and Rosa damascena flowers, providing aroma traits when full bloom is achieved [35,36]. Tocopherols, lipid compounds known for their antioxidant activity and neurological protection [37], have been detected in grapevine flower tissues from the cv.…”
Section: Lipid Profiling Of Grape Bunches During Flowering and Berry ...mentioning
confidence: 99%
“…At flowering, seven metabolites were found to be accumulated, including α-tocopherol, γ-tocopherol, methyl hendecanoic acid, ursolic acid, oleate, 1-docosene, and 9-eicosene (Figure 1C). Volatiles such as 1-docosene and 9-eicosene have been found in the essential oils of Tamarix dioica and Rosa damascena flowers, providing aroma traits when full bloom is achieved [35,36]. Tocopherols, lipid compounds known for their antioxidant activity and neurological protection [37], have been detected in grapevine flower tissues from the cv.…”
Section: Lipid Profiling Of Grape Bunches During Flowering and Berry ...mentioning
confidence: 99%
“…The essential oil yield and components of rose oil are attributed to different environmental and genetic factors. Most of the previous research has been reported on the essential oil variation of R. damascena in different countries including India [ 11 ], Bulgaria [ 12 , 13 ], Iran [ 14 ], and Pakistan [ 15 ]. In most of these studies, the oils were analyzed by GC/MS instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Damask rose (Rosa damascena Mill.) ranks among the top in the list of high-value essential oil crops [1,2]. It is a perennial shrub, which is commercially cultivated in many countries across the world (e.g., Bulgaria, China, Egypt, France, India, Iran, Italy, Morocco, Russia, Turkey, and the USA) [3][4][5].…”
Section: Introductionmentioning
confidence: 99%